FREQUENCY OF SERUM CORTISOL SUPPRESSION IN PATIENTS USING 0.05% CLOBETASOL PROPIONATE AS TOPICAL STEROID FOR MORE THAN 3 WEEKS: Clobetasol Propionate As Topical Steroid - Siddiqui, Muhammad Adeel; Hussain, Majid; Dilnawaz, Mansoor (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the frequency of serum cortisol suppression in patients using 0.05% clobetasol propionate as topical steroid for more than 3 weeks. Study Design: Cross sectional Study. Place and Duration of Study: Both outdoor and indoor patients of Dermatology Department, Military Hospital (MH) Rawalpindi for duration of 6 months i.e. from 18th April 2012 to 17th October 2012 were selected. Patients and Methods: A total of 189 patients were included in the study. Non-probability purposive sampling technique was used. Early morning (0800 hrs) serum for cortisol levels was taken before starting the treatment and same was repeated after 3 weeks at AFIP. Effect modifiers like age and gender were controlled through stratification. The data was analyzed using SPSS version 10. The quantitative variables like age, duration of illness were calculated by taking standard deviation and mean whereas the qualitative variables like gender, suppression of serum cortisol levels were calculated by taking percentages and frequency. Frequency of serum cortisol suppression was presented according to gender and age groups. Results: Majority of the patients selected were between 31-40 years i.e. 44.98% (n=85). Gender distribution was 61.90% (n=117) males and 38.10% (n=72) females. Frequency of serum cortisol suppression in patients using 0.05% Clobetasol propionate as topical steroid for more than 3 weeks was seen in 33.33% (n=63). Conclusion: The frequency of serum cortisol suppression was significantly higher amongst patients using clobetasol propionate 0.05%. Therefore patients prescribed clobetasol propionate 0.05% topically should be checked for serum cortisol suppression regularly if the application is intended to be used for more than 3 weeks.